A method for determining the content of petroleum hydrocarbons in soil - Qin, Haitian; Huang, He (International Journal of Scientific Research and Management (IJSRM), 2021)
In this paper, ultrasonic - centrifugal extraction - infrared oil meter is used to determine petroleum hydrocarbons in soil.The optimal conditions of ultrasonic centrifugal extraction of petroleum hydrocarbons from soil were investigated by using simulated soil from the extraction agent, ultrasonic temperature, ultrasonic time, ultrasonic power, centrifugal speed, centrifugal time and other factors.The results showed that using tetrachloroethylene as extraction agent, the extraction efficiency of three times reached 88.34% with ultrasonic temperature of 30℃, ultrasonic time of 10min, ultrasonic power of 180W, centrifugal speed of 4000rpm and centrifugation time of 20min in 1% oil-contaminated soil.Under these conditions, the recoveries were 78.97%~96.58% and the relative standard deviations (n=5) of the measured values were 3.82%~12.53%.